The frontiers of Europe: [based on papers presented at a colloquium on the frontiers of Europe] - Anderson, Malcolm (Pinter, 1998)
enth.
Includes bibliographical references and index
Keywords: Europe -- Politics and government -- 20th century; Europe -- Boundaries; Europe -- Foreign relations; Europe -- Economic conditions -- 20th century; Konferenzschrift; Aufsatzsammlung; Staatsgrenze; Europa; Internationale Politik; Kulturelle Identität; Politische Identität; Grenzregelung; Europäische Union